The Empowerment of PKK Women in Treating Hypertension Disease at Home in Wonokoyo Village, Beji District, Pasuruan Regency - Moch Bahrudin (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Housewives are one of the pillars of household strength, they have a role as a nurse in the household. Therefore, one of their responsibilities is to make sure their family members are always in a good health. Usually, the role of the mother as a nurse in the household should deal with hypertension problems. Thus, there are different perspectives among mothers to treat hypertension and those differences are needed to intervene as prevention for more severe illnesses, such as heart failure, kidney failure, and stroke. In this situation, the mother has a critical role to treat hypertension and prevent it becomes worse. This activity aims to empower women in a group called Family Welfare Empowerment (PKK) through a program on treating hypertension properly in Wonokoyo Village. The writers use several methods to conduct the empowerment, such as lectures, discussions, questions and answers, and fun games. As a result of this activity, most of the participants are able to understand the definition, criteria, signs and symptoms, and mild treatment of hypertension. There are 3 questions from the participants, they are the processing of healthy food, first aid for hypertension, and how to take hypertension medication. As an outcome of this community service activity, women as part of society could meet family needs one of which is to determine actions in the treatment of hypertension in the household, which in turn reduces the number of complications. Keywords: Wonokoyo, empowerment, hypertension